2017
DOI: 10.1039/c6lc01310d
|View full text |Cite
|
Sign up to set email alerts
|

Cell agglomeration in the wells of a 24-well plate using acoustic streaming

Abstract: Cell agglomeration is essential both to the success of drug testing and to the development of tissue engineering. Here, a MHz-order acoustic wave is used to generate acoustic streaming in the wells of a 24-well plate to drive particle and cell agglomeration. Acoustic streaming is known to manipulate particles in microfluidic devices, and even provide concentration in sessile droplets, but concentration of particles or cells in individual wells has never been shown, principally due to the drag present along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…This, in turn, drives the formation of a toroidal particle ring in the case of a particle‐laden droplet ( Figure ) . Additionally, it has also been shown that the placement of a piezoelectric element at an offset position beneath a chamber of a 24‐well microarray titer plate can be used to transmit the bulk vibration to the base of a well with the aid of a liquid couplant so as to generate a vortical flow in the chamber, although the complexity of the setup—in particular, the mounting of the element at an angle to the well and the electrical connections required to each element (one is required beneath each well)—makes realization difficult, and, as such, addressability of each well in the entire microarray plate was not demonstrated . A more elegant solution employing a hybrid combination of surface and bulk waves for on‐demand individual, sequential, and simultaneous addressability of all the wells in a 96‐well microarray plate will be discussed below …”
Section: Active Actuationmentioning
confidence: 99%
See 3 more Smart Citations
“…This, in turn, drives the formation of a toroidal particle ring in the case of a particle‐laden droplet ( Figure ) . Additionally, it has also been shown that the placement of a piezoelectric element at an offset position beneath a chamber of a 24‐well microarray titer plate can be used to transmit the bulk vibration to the base of a well with the aid of a liquid couplant so as to generate a vortical flow in the chamber, although the complexity of the setup—in particular, the mounting of the element at an angle to the well and the electrical connections required to each element (one is required beneath each well)—makes realization difficult, and, as such, addressability of each well in the entire microarray plate was not demonstrated . A more elegant solution employing a hybrid combination of surface and bulk waves for on‐demand individual, sequential, and simultaneous addressability of all the wells in a 96‐well microarray plate will be discussed below …”
Section: Active Actuationmentioning
confidence: 99%
“…This was then demonstrated for generating microvortexing in the microwells—individually, sequentially or simultaneously—on‐demand for flexible addressability of the microwell titer plates as an attractive alternative to that in ref. ( Figure ) …”
Section: Active Actuationmentioning
confidence: 99%
See 2 more Smart Citations
“…The acoustic waves' attenuation produces a pressure gradient in the direction of wave propagation that generates a time-averaged body force (F B ) on the uid, thereby producing a streaming ow in the form of micro-vortices. Microvortices produced by SAWs have been widely used in microuidic platforms to mix uids, 26 sort particles, 27,28 manipulate cells, 29,30 drive SAW propulsion devices, 31,32 manipulate droplets, [33][34][35] and pump uids using acoustic ows.…”
Section: Introductionmentioning
confidence: 99%